Study guides

☆☆

Q: If 7p plus 5q equals -3 find q when p equals 1?

Write your answer...

Submit

Still have questions?

Related questions

7p+5q=-3, p=1 7Xp+5q=-3 7+5q=-3 5p=-10 p=-2

7+5q = -3 5q = -3-7 5q =-10 q = -2

8p+5 = 11+7p= 8p-7p = 11-5p = 6

14 + 6p = 6 + 7p 8 = p

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

4p+9-7p+2 -3p+11 p = 11/3

7p-2p equals = 5

11p+11

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

15 + 3 = 7p - 4p ie 18 = 3p so p = 6

Equilibrium occurs where Qd = QsQd - 128 + 9p = 0Qd = 128 - 9pQs + 32 - 7p = 0Qs = 7p - 327p - 32 = 128 - 9p16p = 160p = 10

5p + 4y

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

6nx + 7p - 14p + 2nx + 6x = 8nx - 7p + 6x

7P + 9 = 16 + 6P subtract 6P from BOTH sides P + 9 = 16 subtract 9 from both sides P = 7

2p+7p = 9p simplified

5p + 15p + 7p = 27p 5p - 15p + 7p = -3p 5p x 15p + 7p = 75p2 + 7p 5p/15p + 7p = 7p + 1/3

3p +12= 7p 7p-3p=12 12?3=4 p=4

An equation where P = 1

-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r

7p+5t

-3p

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

5p-7q

7p+2 is an algebraic expression. Since it is neither an equation nor an equality, it cannot have a solution or answer.